Social Support and Its Associated Factors among Family Caregivers of Persons with Severe Mental Illness - WANG Ruoxi, SONG Suyi, ZHOU Yongjie, LIU Yifeng (Zhongguo quanke yixue, 2022)
BackgroundUnderstanding the characteristics of social support of family caregivers of persons with severe mental illness, and identifying the associated factors are the preconditions of developing evidence-based intervention strategies to improve social support for this vulnerable group. Among the limited studies concerned family caregivers of patients with severe mental illness, the majority focused on their own individual factors, leaving patient- and family-level associated factors largely under-investigated.ObjectiveTo explore the social support and associated factors among family caregivers of persons with severe mental illness, providing a theoretical basis for the development of evidence-based strategies to enhance the level of social support in this group.MethodsA cross-sectional design was used. Multistage sampling was used to select three tertiary grade A mental health organizations from three cities located in eastern, central, and western China, respectively (one was extracted from each city) , then from which, family caregivers of persons with severe mental illness who received outpatient services between August 2018 and December 2019 were selected, and their family caregivers (n=1 001) were recruited as participants. A self-administered survey was conducted in the family caregivers using a questionnaire〔consisting of two parts: demographics and the Social Support Rating Scale (SSRS) 〕compiled by our research team to collect their individual and family information and social support status, as well as patients' (the care receivers') information. Multiple linear regression was employed to identify associated factors for the total score and domain scores of SSRS.ResultsThe mean total score of SSRS for the family caregivers was (34.4±9.1) . And the mean score for its three domains, subjective social support, objective social support, and social support utilization was (20.3±6.2) , (7.5±2.8) , (6.6±2.3) , respectively. The type of occupation of the caregivers, and the type of mental diseases and stability of symptoms of patients cared by them, as well as mean household monthly income per person were associated with the total score of SSRS for the family caregivers (P<0.05) . Furthermore, marital status and religious belief of caregivers, as well as their relationship with the patients cared by them also affected the total score of SSRS of the family caregivers (P<0.05) . As for the scores of domains of SSRS, they were found to be influenced by the type of occupation of the caregivers, the type of mental diseases and stability of symptoms of patients cared by them, and mean household monthly income per person (P<0.05) . Besides that, gender, marital status, living area (rural or urban) , and religious belief of caregivers, their relationship with patients cared by them, and the amount of family subsidies also affected the score of subjective social support of family caregivers (P<0.05) ; the amount of family subsidies also affected the objective social support score of family caregivers (P<0.05) ; gender and living area (rural or urban) of caregivers, and the amount of family subsidies also affected the score of social support utilization of family caregivers (P<0.05) .ConclusionFamily caregivers of patients with severe mental illness possessed a low level of social support, had limited access to social support, perceived insufficient support, and used social support rather insufficiently. There were differences in factors associated with their overall social support and domain-specific social support. More attention should be paid to family caregivers who are single, unemployed, have low household monthly income per person, care for patients with schizophrenia or unstable mental symptoms, and provide them with support in accordance with their needs, by which their care burden can be alleviated, and their physical and mental health will be improved eventually.